The effect of business support from business incubator towards the performance of entrepreneurs in the early start-up companies in Malaysia with the moderating effect of risk-taking propensity - Mohd Noor Hidayat Jimainal; Ramraini Ali Hassan; Khairiah Mazdiah Kalimin; Rudy Ansar; Brahim Chekima; Lim, Ming Fook (Macrothink Institute, 2022)
The purpose of this study is to examine how the business support offered by business incubators affects the performance of early start-up entrepreneurs Malaysia with risk-taking propensity as the moderating role. Respondents for this study are among graduated entrepreneurs from business incubators that are located at Sarawak, Sabah, Penang, Johor, Kuala Lumpur, and Selangor. The analysis for this study was done based on 100 questionnaires using the Structural Equation Modelling (SEM) technique using Partial Least Squares (PLS). The findings indicated that business support does have positive significant impact on entrepreneur’s performance in the early start-up companies. In contrast, risk-taking propensity as a moderating role does not have significant impact towards entrepreneur’s performance in the early start-up companies in Malaysia. The findings of this study may aid to the policymaker and government as a standard while business incubator is able to understand more about entrepreneurs within the business incubator. Furthermore, other scholars can benefit from this study to serve as a guideline for their future research in similar field of study.